Parasitic infections in the practice of a phthisiologist (clinical case) - V. А. Aksenova; N. I. Klevno; A. V. Kazakov; A. D. Pakhlavonova; E. A. Sokolskaya; S. M. Kavtarashvili; V. A. Romanenko; N. S. Stepanenko (LLC "Diagnostics and Vaccines", 2022)
Parasitic infections are widespread throughout the world and are especially common in childhood. The absence of pathognomonic symptoms in liver diseases is characteristic. We presented clinical observation with asymptomatic echinococcosis with damage to the respiratory organs and liver. During the fluorographic examination, changes in the lungs were revealed, in connection with which she was sent for a consultation with a phthisiatrician. In the TB hospital, with the help of a comprehensive examination and modern telemedicine technologies, changes were identified in lungs and in the liver. This clinical observation showed that it is necessary to conduct a comprehensive examination before prescribing specific anti-tuberculosis treatment. Increasing physicians' knowledge of parasitic diseases could increase the early detection.